Doppler Domain Decomposition of the Underwater Acoustic Channel Response - Ijaz, S. (2015)
Most underwater applications are very sensitive to environmental perturbations like source/receiver motion and surface variations. In real conditions, the transmitted signal reaches the receiver through different paths where each path is affected by different environmental perturbations. Due to the interaction with these environmental variations different Doppler is induced in each path. By observing the Doppler for the whole signal it is not possible to determine the contribution of each environmental variation. The main goal of this paper is to isolate different paths and analyse the effects of the environmental variations on each path in terms of the induced Doppler. A new technique called Time Windowed Doppler Spectrum is proposed which has been found very effective in tracking the Doppler due to each path separately. By using this technique it can be shown that it is possible to distinguish between surface reflected and direct path by observing the Doppler variations associated with each path. The surface induced Doppler was observed using this technique by analysing the temporal evolution of the surface reflected path. The surface variability effects the Doppler in terms of stretching and shortening the path between the transmitter and receiver. The data processed in this paper was acquired during CALCOMM'10 Experiment which took place in June 2010 at the south coast of Portugal.